Strategi Guru dalam Mengatasi Kejenuhan Belajar Siswa Melalui Pemanfaatan Media Pembelajaran Digital di MTs Masalikil Huda Tahunan - Mohammad Nashih; Sukarman; Mustaqim (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2026)
Learning burnout significantly challenges junior high school students, especially within Islamic boarding-school-based environments (madrasahs) dealing with text-heavy religious subjects. This study aims to explore teachers' instructional strategies in mitigating learning burnout through digital learning media integration at MTs Masalikil Huda Tahunan, Jepara. Utilizing a descriptive qualitative case study approach, data were gathered through semi-structured interviews, passive classroom observations, and documentation. Informants were selected via purposive sampling, consisting of subject teachers, curriculum coordinators, school counselors, and representatives of affected students. The collected data were analyzed using Miles, Huberman, and Saldaña’s interactive model, encompassing data condensation, data display, and conclusion drawing. The findings revealed that learning burnout was primarily driven by the cognitive gap between students' dynamic digital consumption habits outside school and monotone expository lecturing methods inside the classroom. To address this, teachers formulated targeted instructional strategies by integrating gamified platforms, deploying interactive digital pocketbooks, and converting the school's proprietary e-learning ecosystem into interactive discussion forums. These interventions effectively restored students' emotional engagement and enhanced cognitive memory retention by offering refreshing and immersive learning stimuli. Although well-supported by robust school broadband infrastructure, teachers faced ongoing challenges, including digital distractions in the classroom and a rising dependency on visual stimuli among students. This study concludes that the long-term efficacy of digital media in overcoming psychological fatigue relies heavily on a balanced pedagogical blend between cyber exploration and traditional deep reading comprehension.